1998
DOI: 10.1046/j.1365-2133.1998.02461.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol cream with or without concurrent topical corticosteroid in psoriasis: tolerability and efficacy

Abstract: The objectives of the study were to determine whether concurrent treatment with calcipotriol (50 microg/g) and either clobetasone 17-butyrate cream (0.5 mg/g) (moderate potency) or betamethasone 17-valerate cream (1 mg/g) (potent) or placebo (vehicle of calcipotriol) was more effective and/or caused less skin irritation than calcipotriol cream (50 microg/g) used twice daily. It was a multicentre, double-blind, parallel group study. Patients applied calcipotriol cream in the morning and either vehicle (n = 174)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 16 publications
4
82
0
4
Order By: Relevance
“…BD is believed to have anti-inflammatory and anti-pruritic actions that are characteristic of corticosteroids. Several studies have shown that combined therapy with products containing these two active substances is more effective than mono therapy, the additive clinical effects and reduced skin irritationmay be achieved [7]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…BD is believed to have anti-inflammatory and anti-pruritic actions that are characteristic of corticosteroids. Several studies have shown that combined therapy with products containing these two active substances is more effective than mono therapy, the additive clinical effects and reduced skin irritationmay be achieved [7]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with the combination ointment gives relevant advantages also in terms of patient's compliance, thanks to the once-daily application, quality oflife parameters and tolerability profile (5-10). The use of combination product may reduce the risk of adverse events associated with the long-term use of corticosteroid monotherapy (atrophy and rebound) as well as the irritation associated with calcipotriol (18,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, its therapeutic efficacy and safety in the treatment of psoriasis vulgaris have been demonstrated in several clinical trials evaluating the drug as either single-drug therapy or in combination with UVB, PUVA, cyclosporin, acitretin or topical corticosteroids [2, 3, 4, 5, 6]. In most trials, the applied amounts of calcipotriol ointment or cream (both 50 µg/g) have been considerably below the recommended dose maximum of 100 g/week.…”
Section: Introductionmentioning
confidence: 99%